2009
DOI: 10.1089/end.2008.0535
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of a Surgeon-Prepared Gelatin Hemostatic Agent Compared with FloSeal for Hemostasis in Laparoscopic Partial Nephrectomy

Abstract: As health care costs continue to rise, delivering high-quality care in a cost-effective manner is paramount. Our study demonstrates similar safety and efficacy of a surgeon-prepared, cheaper gelatin matrix compared with FloSeal. Generic hemostatic agents are a viable alternative to more expensive agents in institutions in which commercially available agents are not available or cost prohibitive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 15 publications
1
19
0
Order By: Relevance
“…A recent survey on the current practice for urologist performing LPN, confirmed that HAs were used in 77.4% of cases and were mainly represented by gelatine‐matrix thrombin (Floseal), fibrin gel (Tisseel), BSA (Bioglue), oxidised regenerated cellulose (Surgicel) or combinations of these. The overall postoperative bleeding requiring transfusion and urine leakage rates were 2.7% and 1.9%, respectively . Triaca et al.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…A recent survey on the current practice for urologist performing LPN, confirmed that HAs were used in 77.4% of cases and were mainly represented by gelatine‐matrix thrombin (Floseal), fibrin gel (Tisseel), BSA (Bioglue), oxidised regenerated cellulose (Surgicel) or combinations of these. The overall postoperative bleeding requiring transfusion and urine leakage rates were 2.7% and 1.9%, respectively . Triaca et al.…”
Section: Discussionmentioning
confidence: 93%
“…A recent survey on the current practice for urologist performing LPN, confirmed that HAs were used in 77.4% of cases and were mainly represented by gelatine-matrix thrombin (Floseal), fibrin gel (Tisseel), BSA (Bioglue), oxidised regenerated cellulose (Surgicel) or combinations of these. The overall postoperative bleeding requiring transfusion and urine leakage rates were 2.7% and 1.9%, respectively [4][5][6][7]. Triaca et al [8] were the first to describe the use of thrombin sealant with no renal artery occlusion in OPN and concluded that PN with no temporary arterial occlusion is technically feasible and safe.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, no impact was seen on operative time, ischemia time, or other negative outcomes. Consequently, the authors suggested that omitting these agents during RAPN could be safe and cost-effective1415. The absolute cost per case may vary between $100–$500, depending on the agent used.…”
Section: Discussionmentioning
confidence: 99%
“… No Floseal ® (laparoscopic suturing) (68) Guzzo 2009 [ 27 ] Floseal ® (19) Operating and warm ischaemia times, blood loss, postoperative transfusion rate, length of hospital stay, and costs Similar safety and efficacy for the two alternatives, and Gelfoam ® was less expensive than Floseal ® . Gelfoam ® (21) Koni 2012 [ 28 ] Floseal ® (11) Differences in complications The use of haemostatic agents significantly reduced postoperative complications. Among haemostatic agents, TachoSil ® provided the best benefits in terms of postoperative complications.…”
Section: Resultsmentioning
confidence: 99%